1997
DOI: 10.1111/j.1460-9568.1997.tb01397.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlations Between Cerebral Protein Synthesis Rates and Deep Sleep in Macaca mulatta

Abstract: Local rates of cerebral protein synthesis (ICPSleu) were determined with the autoradiographic L-[1-14C]leucine method in seven awake and seven asleep, adult rhesus monkeys conditioned to sleep in a restraining chair in a darkened, ventilated chamber while EEG, EOG, and EMG were monitored. Prior to the period of measurement all animals slept for 1-4 h. Controls were awakened after at least one period of rapid-eye-movement (REM) sleep. Experimental animals were allowed to remain asleep, and they exhibited non-RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(86 citation statements)
references
References 35 publications
12
72
0
2
Order By: Relevance
“…37), or by cellular efforts to limit protein turnover in a situation when little new protein is produced. These results in the fly brain are consistent with prior studies in the rat brain that showed a pattern of gene expression changes that would promote increased protein synthesis during sleep compared with wakefulness (15) and are compatible with earlier findings of increased cerebral protein synthesis during sleep compared with wakefulness in mammals (62,68).…”
Section: Discussionsupporting
confidence: 82%
“…37), or by cellular efforts to limit protein turnover in a situation when little new protein is produced. These results in the fly brain are consistent with prior studies in the rat brain that showed a pattern of gene expression changes that would promote increased protein synthesis during sleep compared with wakefulness (15) and are compatible with earlier findings of increased cerebral protein synthesis during sleep compared with wakefulness in mammals (62,68).…”
Section: Discussionsupporting
confidence: 82%
“…We had shown previously that transcript levels of EF2 and the initiation factor 4AII, both key components of the translational machinery, are specifically increased during sleep in the brain but not in peripheral tissues, suggesting that sleep may favor brain protein synthesis ). This conclusion is in agreement with previous studies showing that leucine incorporation is higher during NREM sleep relative to waking in both rats and monkeys (Ramm and Smith, 1990;Nakanishi et al, 1997). Thus, it appears that the high levels of NA during wakefulness may inhibit brain protein synthesis, whereas the decreased release of NA during sleep may facilitate it.…”
Section: Norepinephrine and Protein Synthesissupporting
confidence: 82%
“…Similar relationships between sleep and markers of protein synthesis have also been elucidated in numerous brain regions of the monkey (Nakanishi et al 1997). In addition, Smith et al (1991) have shown that administration of protein synthesis inhibitors during REM sleep windows in rats, thought to be critical for consolidation, prevents behavioral improvement following the sleep period, while groups that receive saline during this time show normal post-sleep learning.…”
Section: Neurochemistrymentioning
confidence: 74%